Phaseolus vulgaris L. var. Venanzio Grown in Tuscany: Chemical Composition and In Vitro Investigation of Potential Effects on Colorectal Cancer - Federica Finetti; Marco Biagi; Jasmine Ercoli; Giulia Macrì; Elisabetta Miraldi; Lorenza Trabalzini (MDPI AG, 2020)
Phaseolus vulgaris L. (common bean) is a leguminous species that is an important dietary component due to its high content of proteins, unsaturated fatty acids, minerals, dietary fibers and vitamins. Due to the high content of polyphenols, several biological activities have been described for bean extracts, making it possible to include P. vulgaris among food with beneficial effects for human health. Moreover, more than 40,000 varieties of beans have been recognised with different nutraceutical properties, pointing out the importance of food biodiversity. In this work, we describe for the first time the chemical composition and biological activity of a newly recognized Italian variety of P. vulgaris grown in a restricted area of the Tuscany region and named "Fagiola di Venanzio". Fagiola di Venanzio water extract is rich in proteins, sugars and polyphenols and displays antioxidant, anti-inflammatory and antiproliferative activities in in vitro assays on colon cancer cellular models. Our data indicate that this variety of P. vulgaris appears to be a promising source of bioactive compounds and encourage more in-depth studies to better elucidate the implications of its consumption for public health.